Documentary Imagery in Modern Non-Fictional Prose - Shakhnoza Berdieva (European Science Publishing, 2023)
The article examines how the image of an outstanding personality is created, where documentary becomes a cementing factor, while highlighting the correlation between the journalistic principle and artistry in the analyzed text.
Keywords: imagery, author's image, creative person, internal organization of the image.